Validation of a smart chair and corresponding smartphone app as an objective measure of desk‐based sitting. Issue 1 (21st January 2019) - Arrogi, Anass; Boen, Filip; Seghers, Jan
Abstract: Objectives: This study evaluated the validity of a smart chair and corresponding smartphone app (chair&app) to measure sitting time and sitting interruptions against camera‐derived observation and activPAL. Methods: Belgian deskbound university employees (n = 28, 17 women, mean age 30 ± 7.5 years, mean BMI 22.1 ± 2.0 kg/m 2 ) were provided with the chair&app in three conditions: a controlled condition (following a prescribed protocol), a free‐living condition (conducting usual office work for 2 hours), and an extended free‐living condition (conducting usual office work for three consecutive days). Total sitting time and the number of sitting interruptions were compared between the chair&app and criterion measures (camera observation and activPAL). Criterion validity was assessed using mean differences (95% CI) and intra‐class correlation coefficients (ICC; 95% CI). Results: In the controlled condition, mean sitting time and number of sitting interruptions differed between chair&app and camera observation by 2.7 (−2.4, 7.9) minutes and −8.0 (−10.4, −5.6) interruptions, respectively. For the free‐living condition, there was good agreement between chair&app and camera observation for both sitting time (ICC: 0.74; 0.28, 0.93) and sitting interruptions (ICC: 0.68; 0.10, 0.91). For the extended free‐living condition, there was excellent agreement between chair&app and activPAL for sitting time (ICC: 0.89; 0.49, 0.97). Meanwhile, there was poor agreement between chair&app and activPAL for sitting interruptions (ICC: 0.38; −0.04, 0.70). Conclusions: Chair&app generally provided reliable measures of desk‐based sitting. Consequently, chair&app might be useful as a self‐monitoring tool in the workplace context. Further research is needed to explore its usefulness in reducing adults' desk‐based sitting.